INCORPORATING BALINESE LOCAL WISDOM INTO PEDAGOGICAL APPROACHES: A CASE STUDY OF JUNIOR HIGH SCHOOLS - Wayan Maba; Ida Bagus Nyoman Mantra; Ida Ayu Made Wedasuwari (International Journal of Social Science, 2025)
This study examines the incorporation of local wisdom into pedagogical approaches in junior high schools in Bali, emphasizing how educators integrate Balinese cultural values and practices into classroom instruction. This research examines the utilization of local wisdom, the teaching methods employed, and the problems faced in various educational environments through culturally responsive pedagogy. A qualitative case study methodology encompassed classroom observations, semi-structured interviews with educators and administrators, and an analysis of instructional documents. Research indicates that Balinese philosophies, such Tri Hita Karana and Tat Twam Asi, and other local wisdom together with community-oriented practices, are amalgamated through storytelling, project-based learning, reflective writing, and experiential instruction. These methodologies promote student involvement, cultural consciousness, and moral advancement. Nonetheless, obstacles hinder its implementation, such as time limitations, the absence of culturally pertinent teaching materials, insufficient professional development, and demands from the conventional curriculum. The study underscores differences in integration methods based on regional and institutional contexts prioritizing reflective and discussion-oriented approaches. The findings confirm that teaching grounded on local wisdom increases the significance and effectiveness of education, while simultaneously acting as a vehicle for cultural preservation. The study advocates for enhanced institutional support, educator training, and curriculum adaptability to foster culturally relevant education.